Antibacterial and antibiofilm activity of Ammi majus seed against Gram-positive bacteria - Adham, Aveen Nozad; Abdulah, Zheen Abdulelah (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Ammi majus belongs to family Apiaceae is an important plant used in a different country traditionally for treatment bacterial infection. This study aimed to investigate in vitro antibacterial and antibiofilm activity of Ammi majus seed extracts against six isolated Gram-positive bacteria. Methods: The antibacterial activity of seed extracts were screened by disk diffusion and agar overlay bioautography method and their activities were further determined by minimum inhibitory and minimum bactericidal concentration. Biofilm formation was evaluated by the microtiter plate crystal violet assay. The quantity of bound bacteria was determined by measuring absorbance at (OD630 nm) using microtiter plate reader. Results: Ethanol 80% and ethyl acetate extracts showed variable activity against all isolated bacteria while petroleum ether extract revealed resistance against studied bacteria. Streptococcus mitis showed more pronounced sensitivity against both extracts by disk diffusion (12 mm and 10 mm) and bioautography method with minimum inhibitory concentration 7.8125 mg/ml of ethanol 80% and 15.625 mg/ml for ethyl acetate extracts. Ethanol 80% and ethyl acetate extract significantly reduced biofilm formation as compared to control, showed antibiofilm activity at 0.4883-62.5 mg/ml and exhibited strongest antibiofim activity against Staphylococcus aureus. Conclusion: Ammi majus seed extracts revealed highest antibacterial activity against Streptococcus species and strongest antibiofilm activity on Staphylococcus species.